(untitled) (Bangladesh Journal of Medical Science, 2014)
Aim: To evaluate the efficacy of oral Theophylline for the management of post dural puncture headache (PDPH). Material and Method: Forty patients with PDPH, whose surgeries were done under spinal anaesthesia, were selected randomly and divided into two groups of 20 each. One group to receive conservative treatment and the other group Theophylline (400 mg) only orally. Intensity of headache was analysed using a visual analogue scale (VAS) of pain. Assessment was done immediately before (0 h) and at 8, 16 and 24th hr of drug administration. Result: Significantly better relief of PDPH was found in Theophylline (9.3±5.7) than the conservative group (56.7 ±10.2) (p<0.001). Recurrence of headache was found in 2 patients (10 %) at 16th hr and 2 (10%) at 24th hr in the Theophylline group compared to 12 (60%) and 14 (70%) patients respectively in the other group. Conclusion: The study concludes that Theophylline in the management of post dural puncture headache may be considered the best choice over the conventional approach. DOI: http://dx.doi.org/10.3329/bjms.v13i2.18292 Bangladesh Journal of Medical Science Vol.13(2) 2014 p.114-118